Pertanggungjawaban Pidana Tenaga Kesehatan Terhadap Malpraktik Dan Negligence Dalam Tindakan Khitan (Sirkumsisi) - Sibarani, Tamara Roully; Effendi, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Errors of Practice (malpractice) occur or caused a malfunction that canbe less cautious, less careful, and less seriousness in the anamnesis, examination,diagnosis, therapy/treatment and follow-up, on the other side because it is lessskilled and lack of knowledge from the healthcare personnel concerned. The studytitled "Criminal Liability for health workers against malpractice and Negligencein Khitan Action (circumcision)", has a formulation of the issue of how healthcriminal liability for malpractice and Negligence in the action of circumcision(circumcision), and how should the ideal arrangement against health workerswho perform malpractice and negligence in the actions of circumcision(circumcision).The purpose of writing this thesis is: First, to know the criminal liability ofhealth workers against malpractice and negligence in the act of circumcision(circumcision). Secondly, to know the ideal setting of health personnel whoperform malpractice and negligence in the action of circumcision (circumcision).This type of research is normative legal research or can also be called bydoctrinal law research. From the results of the research problem there are twopoints that are concluded, firstly, in case the nurse proved and fulfill the elementof doing malpractice or omission in the action of the Kkhitan (circumcision) to thepatient then the nurse can be asked Criminal liability. Secondly, in the Indonesianlegal system speaking of regulations that ideally is a rule that should be or is notdone by health workers (caregivers) in terms of the provision of services ofcircumcision action (circumcision). For the case of circumcision action(circumcision) should be made renewal or policy which contains the extent of therights and obligations to be done by the nurse.Key words: Negligence – Circumcision – Regulation-Ideally